STRATEGI KEPEMIMPINAN KEPALA KUA DALAM MENINGKATKAN KEDISPLINAN PEGAWAI KANTOR URUSAN AGAMA (KUA) DI DESA NAPA KECAMATAN BATANGTORU - Subuh Waldohu Akbar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
In order for employees to obey the regulations that have been decided and enforced by the company, discipline is an action that urges them to comply. In this case, employee discipline can be seen as a kind of training intended to shape and improve employee knowledge, attitudes and behavior in order to encourage other staff members to take an active role in raising their own performance standards. Remembering that people will perform better at work if they are more disciplined. This thesis focuses on the following problem: How does the head of the KUA of the Napa Village Religious Affairs Office, Batangtoru District, improve employee discipline? What aspects of the KUA head's leadership style help or hinder improving employee discipline? The purpose of this research is to determine the leadership approach used by the head of the KUA Office of Religious Affairs in Napa Village, Batangtoru District in improving employee discipline. to determine the driving and inhibiting factors of the KUA head's leadership approach in improving worker discipline at the Napa Village Religious Affairs Office, Batangtoru District. Descriptive research is a type of research conducted. that seeks to understand phenomena—such as motivation, behavior, and perceptions—that study participants encounter. The motivation for this research stems from the researcher's interest in the leadership approach of the head of the KUA in improving the discipline of employees at the Napa Village Religious Affairs Office, Batangtoru District. Research results: The Head of the KUA of Napa Village, Batangtoru District, uses three strategies to improve employee discipline, namely by giving instructions to employees, giving them examples, and holding sharing sessions. The first three supporting criteria are: (1) effective leadership; (2) receive compensation; and (3) punishment. The first two barriers are lack of personal awareness and work procrastination.